[Cu(P^P)(N^N)][PF6] compounds with bis(phosphane) and 6-alkoxy, 6-alkylthio, 6-phenyloxy and 6-phenylthio-substituted 2, 2′-bipyridine ligands for light-emitting electrochemical cells. Issue 31 (30th July 2018) - Alkan-Zambada, Murat; Keller, Sarah; Martínez-Sarti, Laura; Prescimone, Alessandro; Junquera-Hernández, José M.; Constable, Edwin C.; Bolink, Henk J.; Sessolo, Michele; Ortí, Enrique; Housecroft, Catherine E.
Abstract : Bright and stable LECs with [Cu(P^P)(N^N)][PF6 ] complexes containing 6-alkoxy- or 6-phenyloxy-2, 2′-bipyridine ligands. Abstract : We report a series of [Cu(P^P)(N^N)][PF6 ] complexes with P^P = bis(2-(diphenylphosphino)phenyl)ether (POP) or 4, 5-bis(diphenylphosphino)-9, 9-dimethylxanthene (xantphos) and N^N = 6-methoxy-2, 2′-bipyridine (MeObpy), 6-ethoxy-2, 2′-bipyridine (EtObpy), 6-phenyloxy-2, 2′-bipyridine (PhObpy), 6-methylthio-2, 2′-bipyridine (MeSbpy), 6-ethylthio-2, 2′-bipyridine (EtSbpy) and 6-phenylthio-2, 2′-bipyridine (PhSbpy). The single crystal structures of all twelve compounds have been determined and confirm chelating modes for each N^N and P^P ligand, and a distorted tetrahedral geometry for copper(i ). For the xantphos-containing complexes, the asymmetrical bpy ligand is arranged with the 6-substituent lying over the xanthene 'bowl'. The compounds have been characterized in solution by 1 H, 13 C and 31 P NMR spectroscopies, and their photophysical and electrochemical properties are described. They are yellow emitters and solid samples show photoluminescence quantum yields in the range up to 38%, with emission lifetimes ≤10.2 μs. On going from powder to frozen Me-THF, the excited state lifetimes increase which might suggest the presence of thermally activated delayed fluorescence (TADF). All the compounds have been tested in light-emitting electrochemical cells (LECs). Bright and stable LECs are obtained with complexes containing alkoxy- or phenyloxy-substituted ligands, making this family of compounds very relevant for the future development of copper-based electroluminescent devices.